Community prevalence of polycystic ovary syndrome (PCOS) in the Gampaha district, Sri Lanka - Kumarapeli, V.; Yapa, C.; Dodampahala, S.H.; Seneviratne, R De A.; Wijeyaratne, C.N. (My University, 2006)
BACKGROUND: The community prevalence of the PCOS, the commonest endocrine disorder of women of childbearing age, is unknown in Sri Lanka. OBJECTIVE: To assess the prevalence, clinical, biochemical and radiological characteristics of PCOS in the community setting. STUDY DESIGN: Cross sectional study with a nested case control study. STUDY SETTING: Administrative district of Gampaha, Western Province, Sri Lanka. METHOD: Probability proportionate to size, cluster sampling of women of 15-39 years (Census 2001) residing in 4 selected Divisional Secretary areas of urban and rural socio-economic composition, using strict inclusion / exclusion criteria. A pre-tested validated interviewer administered questionnaire (IAQ) evaluated their menstrual history, cutaneous manifestations of PCOS (hirsutism, acne, acanthosis nigricans, temporal balding or androgenic alopecia), and excess weight gain. Probable cases underwent clinical examination, endocrine testing and ovarian ultrasound scanning within the first five days of menses. Clinic records of previously diagnosed PCOS subjects were evaluated. Case definition was based on Rotterdam 2003 revised diagnostic criteria. RESULTS: Study population selected was 3030 women representing the population structure of Gampaha District. Response rate was 2915 (96.2 percent). 220 (7.5 percent) probable cases were identified: 209 (95.0 percent) oligomenaorrhea / amenorrhea, 11 hirsutism with regular cycles. Of them 177 (80.5 percent) participated for clinical and laboratory examination, 150 (68.2 percent) underwent ultrasound scanning, yielding an overall participation rate of 74.5 percent. There were 19 already diagnosed and 152 newly diagnosed cases with PCOS, yielding a prevalence of 5.9 percent (95 percent CI 5.1 percent - 6.8 percent) with hirsutism (FG score >7) 46.3 percent, testosterone >2 SD 5.1 percent, polycystic ovaries (PCO) 88 percent, oligo/ amenorrhea and FG>7 in 46.7 percent, oligo/amenorrhea and testosterone >2SD in 5.9 percent, oligo/amenorrhea and PCO 83.6 percent and hirsutism and PCO 4.6 percent. CONCLUSIONS: The community prevalence of polycystic ovary syndrome in the Gampaha District of Sri Lanka is 5.9 percent with oligomenorrhoea, polycytic ovaries and hirsutism being common characteristics. FUNDING: National Science Foundation, Special Trustees Leeds General Infirmary, UK.
Keywords: PCOS; Gampaha; Sri Lanka